2017
DOI: 10.5354/0719-0581.2017.47947
|View full text |Cite
|
Sign up to set email alerts
|

Conductas y actitudes alimentarias anómalas y calidad de vida relacionada con la salud en niños

Abstract: El propósito de esta investigación fue identificar la presencia de conductas y actitudes alimentarias anómalas (CAAA) y su asociación con el peso corporal y la calidad de vida relacionada con la salud en una muestra infantil. Participaron 398 niños de una escuela pública y tres privadas, 203 mujeres (51%) y 195 varones (49%), quienes contestaron el Test Infantil de Actitudes Alimentarias (ChEAT-26) y el Cuestionario de Calidad de Vida Pediátrica (PedsQL); también se registró su peso y talla para el cálculo del… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

1
2
0
3

Year Published

2021
2021
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(6 citation statements)
references
References 25 publications
1
2
0
3
Order By: Relevance
“…In Mexico, the National Health and Nutrition Survey (ENSANUT) found that in boys and girls between the ages of ten and thirteen, concern about weight gain was more frequent, with 11.4% and 11.3%, followed by overeating with 10% and 9.9%, and loss of control over eating, with 7% and 5.8% respectively (ENSANUT, 2006). Franco-Paredes et al (2017) found that in children aged ten and eleven with overweight and obesity, DEB occurred in 22.9% and 15.9% respectively [9], which coincides with the data reported internationally [10].…”
Section: Introductionsupporting
confidence: 73%
“…In Mexico, the National Health and Nutrition Survey (ENSANUT) found that in boys and girls between the ages of ten and thirteen, concern about weight gain was more frequent, with 11.4% and 11.3%, followed by overeating with 10% and 9.9%, and loss of control over eating, with 7% and 5.8% respectively (ENSANUT, 2006). Franco-Paredes et al (2017) found that in children aged ten and eleven with overweight and obesity, DEB occurred in 22.9% and 15.9% respectively [9], which coincides with the data reported internationally [10].…”
Section: Introductionsupporting
confidence: 73%
“…He de ahí la importancia de identificar las conductas y cogniciones de la conducta alimentaria en edades tempranas en vista de que tienen mayor riesgo de desarrollar algún TCA severo en edades adultas (Franco-Paredes et al, 2017). La imagen corporal percibida como una estimación del estado nutricional, tal vez podría aplicarse como una medida indirecta de la adiposidad entre los hombres delgados y entre las mujeres delgadas y con sobrepeso (Sánchez-Villegas et al, 2001).…”
Section: Introductionunclassified
“…Las cogniciones adquiridas sobre la imagen corporal tienen una relación directa en las etapas de formación (Franco-Paredes et al, 2017) en particular en la educación secundaria, por lo que en el presente trabajo de investigación realizamos la caracterización de los trastornos de conducta alimentaria según el sexo, según IMC, y determinamos la prevalencia de este trastorno.…”
Section: Introductionunclassified
“…Hence, it is important to identify eating behaviors and cognitions at early ages taking into account that they are at higher risk of developing severe ED in adulthood (Franco-Paredes et al, 2017). Perceived body image as an estimate of nutritional status could perhaps be applied as an indirect measure of adiposity among lean men and lean and overweight women (Sánchez-Villegas et al, 2001).…”
Section: Introductionmentioning
confidence: 99%
“…Acquired cognitions about body image have a direct relationship in the formative stages (Franco-Paredes et al, 2017) principally in secondary education, so in the present research work, we performed the characterization of eating disorders according to sex, according to BMI, and determined the prevalence of this disorder.…”
Section: Introductionmentioning
confidence: 99%